New Stained Glass : The Museum of Contemporary Crafts of the American Crafts Council : January 28, 1978 - April 2, 1978. - Shea, Judith (New York : Museum of Contemporary Crafts of the American Crafts Council, 1978)
Barnett, Sanford ; Edwards, Garth ; Elskus, Albinas ; Kehlmann, Robert ; King, Ray ; Lewis, Casey ; Marioni, Paul ; Mollica, Peter ; Posner, Richard ; Quagliata, Narcissus
New Stained Glass, The Museum of Contemporary Crafts of the American Crafts Council, New York, January 28, 1978 - April 2, 1978
boek